2020
DOI: 10.1148/radiol.2020191842
|View full text |Cite|
|
Sign up to set email alerts
|

Intraoperative Complications of Endovascular Treatment of Intracranial Aneurysms with Coiling or Balloon-assisted Coiling in a Prospective Multicenter Cohort of 1088 Participants: Analysis of Recanalization after Endovascular Treatment of Intracranial Aneurysm (ARETA) Study

Abstract: D espite important technical developments (flow diversion, flow disruption) in the endovascular treatment of intracranial aneurysms, coiling and balloon-assisted coiling (BAC) remain the first-line treatment in management of ruptured and unruptured aneurysm (1,2). Intraoperative neurologic complications have been evaluated in several prospective multicenter series and randomized controlled trials, but the number of participants has typically been relatively small. Additionally, the majority of studies ended pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…In reality, when aneurysms are treated by specialized teams, the risk of treatment is currently significantly lower than even a decade earlier. The prospective multicenter Analysis of Treatment by Endovascular Approach of Nonruptured Aneurysms (ATENA) 34 and Analysis of Recanalization after Endovascular Treatment of Intracranial Aneurysm (ARETA) 35 studies have reported rates of major complications of respectively 2.2% and 1.1%.…”
Section: Discussionmentioning
confidence: 99%
“…In reality, when aneurysms are treated by specialized teams, the risk of treatment is currently significantly lower than even a decade earlier. The prospective multicenter Analysis of Treatment by Endovascular Approach of Nonruptured Aneurysms (ATENA) 34 and Analysis of Recanalization after Endovascular Treatment of Intracranial Aneurysm (ARETA) 35 studies have reported rates of major complications of respectively 2.2% and 1.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from analyses of intraoperative complications in the ARETA study occurring during aneurysm treatment have already been published. 10 However, several complications occur after endovascular treatment of intracranial aneurysms, including: delayed aneurysm rupture inducing rebleeding in ruptured aneurysms, bleeding in unruptured aneurysms, thromboembolic events, and delayed remote hematomas. 4 While delayed bleeding of UIA is rare during the year following aneurysm treatment, rebleeding of RIA can occur within 3 days (acute bleeding), 30 days (early rebleeding), or later (late rebleeding) following aneurysm treatment.…”
Section: Hemorrhagic Strokementioning
confidence: 99%
“…For the treatment of cerebral aneurysms, craniotomy clipping presents greater surgical trauma and risk, while endovascular interventional therapy achieves occlusion of intracranial aneurysms by implanting stents into the aneurysm and releasing a coil. Due to its minimally invasive nature, safety, and effectiveness, it has been widely used in clinical practice in recent years [4,[15][16][17][18][19]. Cerebral aneurysm embolization is an intravascular operation associated with mild stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…With the popularization of endovascular techniques, interventional embolization of unruptured cerebral aneurysms with general anesthesia under digital subtraction angiography (DSA) has become the primary treatment [1][2][3][4][5][6]. In order to avoid aneurysm rupture and bleeding, the maintenance of hemodynamic stability during the perioperative period is important factor that should be taken into account [7,8].…”
Section: Introductionmentioning
confidence: 99%